Implementing the Lexical Approach with Integrated Learning Activities with Thai EFL University Students - Thuratham, Wadinlada (rEFLections, 2024)
This study implemented the lexical approach (LA) with integrated learning activities (ILAs) to determine its effectiveness in enhancing EFL university students’ linguistic knowledge and English communication skills. The objectives were twofold: 1) to assess student progress in language achievement, specifically in English grammar and vocabulary used in everyday conversation, and 2) to investigate student attitudes towards the LA with ILAs in developing their English communication skills. Forty-nine English major students from a Thai higher educational institution participated in this study. Data were collected using two research instruments: a language achievement test and a questionnaire. The data were analyzed using Microsoft Excel to calculate percentages and SPSS to examine mean scores and standard deviations. Results from a paired t-test showed statistically significant differences between the pre-test and post-test scores at the .05 confidence level, confirming that the students made progress in language achievement. The LA with ILAs significantly improved students’ knowledge of English grammar and vocabulary used in daily conversation. Moreover, the questionnaire results indicated that students believed the LA with ILAs enhanced their English communication skills, particularly in speaking, followed by reading, listening, and writing skills, respectively. Therefore, the LA with ILAs could be an effective teaching method for EFL educators to reinforce students’ linguistic knowledge and communication skills. With adequate knowledge and skills in an authentic learning environment, students will gain confidence in communicating with foreigners in real-life situations in the future.